Power or Economic Law? Fresh Reflections on ECB Policy - Carl-Ludwig Holtfrerich (Intereconomics, 2018)
Conventional wisdom says that central banks determine interest rate levels. After all, monetary policy set by central banks directly influences money market conditions. But these conditions are also shaped by other actors such as government, manufacturing businesses, commercial banks and non-bank financial institutions, as well as by monetary developments abroad. In this paper, it is argued that market forces, such as a global saving glut, play a more important role in setting interest rates than central banks.
Keywords: 330